Pathology of the peripheral circulation in chronic heart failure - A. T. Teplyakov; V. V. Kalyuzhin; E. V. Kalyuzhina; G. E. Chernogoryuk; M. I. Rachkovsky; I. D. Bespalova; N. N. Terentyeva; I. K. Livshits; M. A. Solovtsov; G. M. Chernjavskaja (Бюллетень сибирской медицины)
In the mechanisms of chronic heart failure (CHF) the key role traditionally given to a violation of intracardiac haemocirculation. Thus, in the guidelines for the evaluation and management of chronic heart failure in the adult, experts of the American College of Cardiology and the American Heart Association (2001-2013) define CHF as «a complex clinical syndrome that can result from any structural or functional cardiac disorder that impairs the ability of the ventricle to fill with or eject blood». Usually rightly believe that than the expression of inotropic and/or lusitropic failure of the appropriate ventricle in patients with CHF, the generally lower of him quality of life and a worse prognosis. However, the severity of the clinical manifestations of heart failure, on the one hand, and reducing the level of satisfaction with life - on the other, is not always depends only on the state of intracardiac hemodynamics. The authors of the review have analyzed papers published on the problem of the pathology of the peripheral circulation in CHF. Consistently examines the role of peripheral vascular remodeling and increased arterial stiffness, endothelial dysfunction of major and resistance arteries, as well as pathology of microcirculation. It has been shown that the development and progression of heart failure is accompanied by a deterioration in the peripheral circulation due to the remodeling of arteries muscular-elastic type and veins with a reduction in vascular dilatation reserve, increase of regional vascular resistance and venous tone, disturbances of tissue transcapillary exchange of oxygen and activate of procoagulant properties of blood. The significance of the effects of vasoconstrictor neurohormonal systems and inflammation in mechanisms of disorders of peripheral circulation in patients with CHF, particularly associated with the metabolic syndrome, have discussed.